Determinants of Adherence to Antiretroviral Therapy among HIV-Infected Patients in Africa - Ayalu A. Reda; Sibhatu Biadgilign (AIDS Research and Treatment)
Background. There are only a few comprehensive studies of adherence to ART and its challenges in Africa. This paper aims to assess the evidence on the challenges and prospects of ART adherence in sub-Saharan Africa. Methods. The authors reviewed original and review articles involving HIV-positive individuals that measured adherence to ART and its predictors in the past decade. Findings. Against expectations, sub-Saharan Africa patients have similar or higher adherence levels compared to those of developed countries. The challenges to ART adherence include factors related to patients and their families, socioeconomic factors, medication, and healthcare systems. Conclusion. Despite good adherence and program-related findings, antiretroviral treatment is challenged by a range of hierarchical and interrelated factors. There is substantial room for improvement of ART programs in sub-Sahara African countries.